Knowledge and Attitudes of Pregnant Women in Giving Early Breastfeeding Initiation (IMD) to Babies - Ratna Dewi; Erike Septa Prautami (Science Midwifery, 2020)
Early Breastfeeding Initiation is the process of a baby breastfeeding immediately after birth, where the baby is allowed to find its mother's nipples, early breastfeeding initiation will greatly help in the continuation of exclusive breastfeeding. This research is an analytical survey research with a cross sectional design, namely research conducted by observing simultaneously to find out the independent and dependent variables. The results of the chi square test showed a p-value of 0.005 <0.05, this indicates that there is a relationship between the knowledge and attitudes of pregnant women about IMD. The conclusion in this study is that most respondents have knowledge about EBI in the good category, namely as many as 20 respondents (62.5%), some respondents have attitudes about IMD in the positive category, namely 17 respondents (53.1%), and there is a relationship between knowledge and attitudes of pregnant women about IMD (p-value = 0.005).